STRATEGY FOR IMPROVING THE COMMUNITY ECONOMY THROUGH ENVIRONMENTALLY BASED TOURISM AND SOCIAL MEDIA IN NAGARI SUNGAI PINANG, WEST SUMATRA PROVINCE - Indraddin, Indraddin; Anggraini, Retno; Irwan, Irwan (Universitas Padjadjaran, 2024)
This research aims to identify strategies to improve the community’s economy through environmentally based tourism and social media in Nagari Sungai Pinang, Pesisir Selatan Regency, West Sumatra. This study used qualitative methods with observation, in-depth interviews, utilization of documentation, and FGD. As an analytical tool, this research used Anthony Giddens’ structural theory of observation practice which is not only determined by the agent but also by structure. According to the research findings, the strategy for improving the community’s economy through environmentally based tourism and social media can be seen in the utilization of the community’s diverse tourism business potential, which includes tourism beaches, tourism mangrove forests, tourism nautical (sea), and tour island. Homestay, Manjuto Beach, and attractive islands such as Pamuntusan Island, Pagang, Marrak, Karanggo, and Erong Bay have all contributed to the growth of business tourism. Its development is aided by local institutions and local expertise from an environmental standpoint. There are other opportunities for enterprises that may be established without damaging natural beauty, including tourist firms that involve underprivileged people. The strategy for enhancing the economy of the public is to include all components from the outset, given that the location is common land in line with the customs that apply in the community of Minangkabau West Sumatera. Apart from that, social media is also used as a promotional tool by involving the younger generation.